Thrust and Torque Analysis on Propeller C4-40 with The Addition of Kort Nozzle to Pitch Variation - Arief, Irfan Syarief; Baidowi, Achmad; Ulfa, Maria (International Journal of Marine Engineering Innovation and Research, 2025)
At this time there are various types of propellers, one of which is the CPP propeller (Controllable pitch propeller). The CPP propeller can change pitch angles, and at certain pitches it can pull the ship backwards without having to change the rotation. But keep in mind that the CPP has only one pitch design where changing the pitch position means reducing the efficiency of the propeller. So it takes a kort nozzle to increase efficiency. The addition of a kort nozzle is one of the developments of an Energy Saving Device (ESD) which in addition to increasing efficiency it is also able to increase the thrust. Problem formulation of this research is to find out changes in thrust, torque and efficiency on the propeller CPP C4-40 after the addition of kort nozzle 37. This research begins with determining the dimensions of the propeller, also the types and dimensions of the nozzle. Then the design and drawing of the propeller C4-40 with a kort nozzle 37 was carried out for pitch changes of 0°, 22.5° and 45°. The next step is a meshing process where each pitch the number of meshing ranges from 2.3 to 3.5 million cells. The last step is to simulate the performance of the propeller with the nozzle using software based on Computational Fluid Dynamic. From this research, it can be concluded that the addition of kort nozzle 37 on the propeller C4-40 changes the thrust, torque and efficiency values significantly. Thrust only increased at pitch 0° J 1.4 and pitch 22.5°. The greatest increase in thrust at pitch 22.5° J 0.6 is 88.74%. Torque is reduced except for pitch 0° J 0.8-1.4. The biggest decrease in torque at pitch 45° J 1.2 is 83%. Meanwhile efficiency has decreased at all pitch angles. Where the biggest decrease in pitch 45° J 1 is 99.83%.